A review on the air-to-air heat and mass exchanger technologies for building applications. (August 2017) - Zeng, Cheng; Liu, Shuli; Shukla, Ashish
Abstract: In this paper, a review on recent development of air-to-air heat and mass recovery technologies has been presented. An extensive investigation on the heat and mass exchanger integrated in energy efficient systems of buildings has been taken through passive systems, mechanical ventilation systems, defrosting methods and dehumidification systems. Applications, advantages, disadvantages and key performance criteria of the each are detailed in the paper. Review paper has found out that; 1) with the combination of passive systems/design such as wind tower and building structure, applications of heat exchangers present insufficient airflow control and real life evaluation; 2) when heat and mass exchangers applied in mechanical ventilation systems, issues such as pressure leakage, air shortcuts and noise should be given significant importance; 3) defrosting is another question to be answered for the heat exchangers operating in cold climates, which, only few innovative defrosting method has been proposed; and 4) with regard to dehumidification systems, heat and mass exchangers face the problems of extra heat in processed air and lack of effective control in dehumidification and regeneration cycle.